Within- and between-person and group variance in behavior and beliefs in cross-cultural longitudinal data - Kirby Deater-Deckard (2018)
© 2017 The Foundation for Professionals in Services for Adolescents This study grapples with what it means to be part of a cultural group, from a statistical modeling perspective. The method we present compares within- and between-cultural group variability, in behaviors in families. We demonstrate the method using a cross-cultural study of adolescent development and parenting, involving three biennial waves of longitudinal data from 1296 eight-year-olds and their parents (multiple cultures in nine countries). Family members completed surveys about parental negativity and positivity, child academic and social-emotional adjustment, and attitudes about parenting and adolescent behavior. Variance estimates were computed at the cultural group, person, and within-person level using multilevel models. Of the longitudinally consistent variance, most was within and not between cultural groups—although there was a wide range of between-group differences. This approach to quantifying cultural group variability may prove valuable when applied to quantitative studies of acculturation.